Vaccination of Children with Thymus Pathology - M. P. Ustinov; A. A. Tarasova (Эпидемиология и вакцинопрофилактика, 2016)
Presented the recommendations for vaccination, depending on the severity of the pathology of the thymus gland. Highlighted post-vaccination period and the formation of specific immunity.